PENERAPAN METODE JIGSAW PADA PEMBELAJARAN MENULIS TEKS BIOGRAFI SISWA SMA - Erna Sri Rahayu; Siti Nurjanah; Yeni Rostikawati (IKIP Siliwangi, 2019)
This research was motivated by the existence of data from the results of observations in the field, which resulted in the ability to write biographical texts on high school students who were still low. This is because there are teacher problems that are not appropriate in applying the method, so students feel difficulties in learning in school. Based on the description, the researchers conducted a study of the application of the jigsaw method to learning to write biographical texts of high school students expected by using these methods to obtain better results. The purpose to be obtained is to find out the process of students using the jigsaw method and to find out the differences in the learning outcomes of writing biographical texts using the jigsaw method. This study also used the Quasi Experimental Design research method with a one group pre-test post-test design approach. The researcher chose 35 high school students in the sample. Data collection techniques were used by conducting the initial test (pretest) and the final test (posttest). Based on these results the average value of pretest is 60.7 and the average posttest value is 80.91 so that there is a difference in value of 20.21 which can be concluded that the jigsaw method is effective in solving teacher problems that are not appropriate in applying the method.